The Effect of Different Glucose Concentrations on the Antiproliferative Activity of Metformin in MCF-7 Breast Cancer Cells - Sholpan Nurzhan; Zhibek Bekezhankyzy; Hong Ding; Nurken Berdigaliyev; Shynggys Sergazy; Alexander Gulyayev; Zarina Shulgau; Christopher R. Triggle; Mohamad Aljofan (MDPI AG, 2023)
The glucose-lowering drug metformin has been reported to have anticancer properties through unknown mechanisms. Other unknown factors that may influence its anticancer potential include the glycemic status of the patient. Therefore, the objective of this study is to determine the effect of different glucose environments on the antiproliferative potency and the cellular mechanism of action of metformin. Human breast cancer cells, MCF-7, were incubated in low, normal, elevated, and high glucose environments and treated with metformin. The antiproliferative potential of metformin and its effect on protein expression as well as its ability to induce cellular apoptosis and autophagy under different glucose environments, were determined using different molecular techniques. Metformin significantly inhibited cellular proliferation in a time- and glucose-concentration-dependent manner. In comparison to elevated glucose, low normal glucose alone induced a significant level of autophagy that was further increased in the presence of metformin. While glucose concentration did not appear to have an effect on the antiproliferative potency of metformin, the cellular basis of action was shown to be glucose-dependent. The antiproliferative mechanism of action of metformin in elevated and low normal glucose environments is mTOR-dependent, whereas, in the high glucose environment, the antiproliferative mechanism is independent of mTOR. This is the first study to report that both the antiproliferative potency and the cellular mechanism of action aredependent on the concentration of glucose.